1994
DOI: 10.1063/1.467419
|View full text |Cite
|
Sign up to set email alerts
|

Structure and energetics of van der Waals complexes of carbon monoxide with rare gases. He–CO and Ar–CO

Abstract: The potential energy surfaces for Ar–CO and He–CO were calculated at the fourth order Mo/ller–Plesset perturbation theory and analyzed using perturbation theory of intermolecular forces. Both the complexes reveal only one minimum related to the approximately T-shaped geometry. For Ar–CO, our best ab initio estimates of Re and De are 3.70 Å and 496 μhartrees, respectively, and the optimal angle Rg–com–O is about 80°. For He–CO, our best Re and De are 3.4 Å and 100 μhartrees, respectively, at the optimal angle R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…[12][13][14] Thachuk et al 1 and Dham and Meath 15 subsequently tested the different potentials' predictions against several experimental observables and found that the XC͑fit͒ potential was at least as good as the others.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Thachuk et al 1 and Dham and Meath 15 subsequently tested the different potentials' predictions against several experimental observables and found that the XC͑fit͒ potential was at least as good as the others.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12]28 The improvement of detection techniques 29,30 and development of the PES [31][32][33] went through several refinement cycles. Finally, an acceptable agreement between theory and experiment has been reached in different parts of the desired broad range of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The Ar-CO complex can be considered a prototype van der Waals system, as witnessed by the extensive experimental [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31] work on its description. For example, the first paper, published in 1978 by Parker and Pack, 20 used Ar-CO as a model system for the development of electron gas methods for calculating intermolecular potential energy surfaces ͑IPESs͒.…”
Section: Introductionmentioning
confidence: 99%